HUBUNGAN ANTARA TINGGI DAN TIPE HAK SEPATU DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PRAMUNIAGA DI DEPARTMENT STORE X, SEMARANG - Ira Destiana; Baju Widjasena; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Height and type of the heel is one of the factors that affect the incidence of low back pain due to postural changes. Wearing high heels lead to changes in posture since the whole weight fall forward away from the line of gravity. The compensation body which carried the heavier, more curved spine and pressure on the lower back muscles. The purpose of this study was to determine the relationship between the height and the type of heel with low back pain complaints of saleswoman in Department Store X, Semarang. This research was a quantitative study with cross sectional approach. The independent variable consists of height and type of high heels while the dependent variable consists of low back pain complaint. External variables studied are based on work period and body mass index. This study differs from previous studies because this study aimed to analyze the variables of type heels and use a visual analog scale to determine the pain that was felt. Population in this research was the saleswoman who wearing high heels as much as 232 people. Based on inclusion and exclusion criteria then obtained a sample of 52 people. Analysis of data used univariate and bivariate analysis with chi square test. The results showed that there was a relationship between the height of heel with low back pain and there was a relationship between the type of heel with low back pain. Department Store X should provide a new policy to use of shoes with 5 cm maximum height and using wedges with higher back in order to reduce low back pain.